Efektivitas Metode Video Dibandingkan Metode Ceramah terhadap Pengetahuan Ibu Hamil Tentang Deteksi Dini Risiko Tinggi Kehamilan di UPTD Puskesmas Jaya Baru Kota Banda Aceh : Penelitian - Khairatunnisa; Dian Maya Sari Siregar; Sapriadi; Yunita (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
High-risk pregnancy is a pregnancy condition that occurs deviation from normal, which directly causes morbidity and mortality of both mother and baby. Of the 11 community health centers working areas, the lowest achievement of high-risk pregnancy events is the Jaya Baru Community Health Center with 51.66% or 62 pregnant women out of 120 pregnant women. The purpose of this study was to determine the effectiveness of the video method compared to the lecture method on pregnant women's knowledge about early detection of high-risk pregnancies in pregnant women. The study used the Quasi-Experimental Design method with a Pretest-Posttest Group Design. The study population was all 54 pregnant women with a sample using a total population technique of 54 people. Data analysis used univariate and bivariate analysis with an independent sample t-test. The results of the independent sample t-test obtained a mean value of knowledge about early detection of high-risk pregnancies using the video method of 9.426 and a mean value of knowledge using the lecture method of 9.130. The video method is more effective in increasing pregnant women's knowledge about early detection of high-risk pregnancies compared to the lecture method at the Jaya Baru Community Health Center in Banda Aceh City.